2007
DOI: 10.1063/1.2735397
|View full text |Cite
|
Sign up to set email alerts
|

Copper selenide nanowires and nanocrystallites in alumina: Carrier relaxation, recombination, and trapping

Abstract: Nonequilibrium carrier dynamics in copper selenide (Cu2−δSe δ=0.15, Cu3Se2) nanowires (diameter ≈18 nm, height ≈2 μm) and nanocrystallites (diameter≈18 nm) in femto- and picosecond time domains by the means of a transient dynamic grating technique were investigated. Bulk and quantum confinement approaches were used to fit the experimental results using nonequilibrium carrier fast relaxation, recombination, and trapping mechanisms. A nonradiative Auger recombination was concluded to be the main mechanism of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
2
11
1
Order By: Relevance
“…This estimation gives that about 9500 e-h pairs were created in a single nw under 23 mJ/cm 2 intensity excitation with 1.55 eV energy pulses, while at the lowest used intensity of 0.63 mJ/cm 2 about 260 e-h pairs were created. In earlier studies of the copper selenide nanostructures it was concluded that a nonradiative Auger recombination is a dominant mechanism at the early stages of the nonequilibrium carrier relaxation [15]. However, our results are in contradiction to this conclusion since the obtained initial decay rates are getting slower with the increase in the excitation intensity.…”
Section: Discussioncontrasting
confidence: 84%
“…This estimation gives that about 9500 e-h pairs were created in a single nw under 23 mJ/cm 2 intensity excitation with 1.55 eV energy pulses, while at the lowest used intensity of 0.63 mJ/cm 2 about 260 e-h pairs were created. In earlier studies of the copper selenide nanostructures it was concluded that a nonradiative Auger recombination is a dominant mechanism at the early stages of the nonequilibrium carrier relaxation [15]. However, our results are in contradiction to this conclusion since the obtained initial decay rates are getting slower with the increase in the excitation intensity.…”
Section: Discussioncontrasting
confidence: 84%
“…It is reasonable to mention that similar solution has been suggested by us earlier for porous alumina coloring [11][12][13][14]. As seen, in this solution under the constant AC peak-to-peak voltage (U p-to-p ) mode, densely packed crystallites in size of from 60 to 160 nm appear to be deposited mainly at the TiNT film surface.…”
Section: Characterizationsupporting
confidence: 51%
“…No reports, however, have been dedicated to the application of p-type selenide species that can be organized in both stoichiometric (CuSe, Cu 2 Se, CuSe 2 , Cu 2 Se 3 ) or non-stoichiometric (Cu 2-x Se) composition. As reported previously, copper selenide nanowired arrays encased in alumina matrices and glasses behave as a direct band gap of 2.2 to 2.4 eV and an indirect band gap of 1.1-1.7 eV light absorbers [11][12][13][14][15]. Therefore, in this study, we attempted to couple copper selenide species with TiO 2 by alternating current (AC) deposition from appropriate aqueous solution comprising Cu 2?…”
Section: Introductionmentioning
confidence: 93%
“…tion peak in near-IR, which leads to optical nonlinearity effects [10]. The observed absorption range appears to be consistent with the first harmonic of YAG type solid state laser (wavelength within 1-1.5 µm).…”
supporting
confidence: 53%
“…Under ambient conditions the material exists as a series of stable and metastable phases, with the stoichiometry coefficients x and y varying from 1 to 3. Variation in stoichiometry results in change of crystalline structure, absorption spectra, and both direct and indirect band gap E g,dir , E g,indir values [10]. Moreover, the crystalline structure and phase composition of copper selenide leads to different optical and other properties obtainable by annealing of specimens.…”
mentioning
confidence: 99%